Analisis Impor Propinsi Sumatera Utara - Dewi Mahrani Rangkuty; Anwar Sanusi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This research aimed to analyze Import North Sumatera for causality and cointegration method between Import, GDRP North Sumatera, Exchange rate and inflation during the period 1990-2015 for short and long term equilibrium relationship. From the results of causality test indicate GDRP North Sumatera had two way causality to Import North Sumatera. Import cause of GDRP North Sumatera and otherwise GDRP cause of Import North Sumatera. Cointegration test and Error Correction Mechanism indicate GDRP North Sumatera as positively and significant influence Import for short and long term equilibrium relationship for during the period 1990-2015. Whereas exchange rate and inflation had one way causality to Import North Sumatera. To Indonesia Government regulation hopely can control import product especially North Sumatera. High GDRP North Sumatera value can used to increasing other activities economic like development financing local. We need import but no dependency, import cause for resources not available in domestic or local. The Indonesia oriented sure keep on the import value every year of time for high GDRP value